Leadership Function in Employee Placement Process at PT. Duta Mandiri Palembang - Ahmad Yani Kosali (Journal of World Conference (JWC), 2021)
This research was conducted to determine the function of leadership in the process of placing employees at PT. Duta Mandiri Palembang, of course, requires a variety of instruments, ranging from facilities and infrastructure to human resources, as well as the character of a leader. The character of a leader and the function of a leader itself is one of the main factors in the management of an organization, both government and private. The method used in this research is descriptive qualitative research method, in which the researcher collects data obtained from the sources studied through observation, interviews, and documentation related to the research title.From the research results, it is known that employees at PT. Duta Mandiri Palembang has been able to describe the policies given by the leadership in the form of a positive response to the duties and responsibilities given to them.